Respuesta :

Jgv(hsbhbsjsnubsjnsugxjbhsbiwnn7gbdj shvshdnsjm
cairde

Answer:

The intermediate step is determining what a is, knowing also that (x+a)²=x²+(2a)x+a².

Also, x²-16x= -68 (in the form (x+a)²=b) is (x-8)²=-4

Step-by-step explanation:

x²-16x=-68

x²-16x+68=0

I suppose the intermediate step is finding (x+a)².

Remember that (x+a)²=x²+(2a)x+a², so 'a' will be half the coefficient of x (number beside x, not x²). The coefficient of x here is -16, so a is -8.

(x-8)²=x²-16x+64

So, if we can create 'x²-16x+64' out of 'x²-16x+68', we'll be on our way:

x²-16x+68=0

(x²-16x+64)+4=0

(x-8)²+4=0

(x-8)²=-4